People, Machines, Enterprises and AI Unite for Impactful Change - Dwi, Mariyono; Hidayatullah, Akmal Nur Alif (Journal of Ecohumanism, 2024)
The objective of this research is to investigate how AI and human intelligence can collaborate in social entrepreneurship to maximize efficiency and promote innovation, all while upholding ethical standards. This study aims to investigate the integration of AI and human intelligence in social entrepreneurship, examining the potential advantages, ethical challenges, and the general impact on innovative solutions for social issues. It seeks to offer insights into how this collaboration can be managed responsibly to establish sustainable and inclusive entrepreneurial environments. Systematic, comprehensive literature review and case study analysis based on PubMed, JSTOR, and Google Scholar data. Thematic analysis identified recurring themes and insights regarding ethical challenges and best practices in integrating AI, human intelligence, and corporate operations. It examines various scientific projects and articles on AI-human collaboration, ethical considerations, and practical implications. This research synthesizes findings from current research and theoretical perspectives to provide a holistic understanding of the topic. The study reveals that integrating AI and human intelligence enhances decision-making, innovation, and operational efficiency, but also poses ethical challenges like data privacy and algorithmic bias. It emphasizes effective collaboration and ongoing workforce development in social entrepreneurship. Projects like "Innovation Farms" demonstrate successful AI-human collaboration in solving social problems. However, it highlights the need for transparency, accountability, and ongoing monitoring for responsible AI implementation. This research explores AI’s ethical and sustainable use in social entrepreneurship, focusing on the balance between automation and human-centered approaches. It provides in-depth information on the practical and ethical impacts of AI applications and offers a sophisticated examination of the fusion of AI and human intelligence. The report offers suggestions for responsible AI use, highlighting the creative potential and moral dilemmas, and is useful for researchers, social entrepreneurs, and legislators interested in AI for social good.